Diversity and Abundance of Breeding Birds, Habitat, and Nesting Substrate Selection in Urban Areas: A Relevant Case from the Southern Slope of the Mediterranean - Douini, Ikram; Squalli, Wafae; Mansouri, Ismail; Mounir, Mohamed; Benka, El-Mostafa; Dakki, Mohamed; Hammada, Soumaya (International Journal of Zoology, 2023)
Urban areas may affect the richness of avian species. The abundance and diversity of urban landscapes offer breeding habitats and nesting resources for urban-adapted species. In our study, we investigated the breeding birds in urban landscapes of Fez’s historical city (Morocco). We used line-transects to search for nests of breeding species, populations, and habitats counting breeding sites and predicting factors (foraging, nesting resources, and urbanization). Furthermore, four habitats counting green gardens, old city walls, urban farms, and urban forests were prospected to search for nests of breeding birds. Among 13 breeding species including 12 resident-breeders, and one breeding migrant, a total of 109 nests were documented. Five species counting Turdus merula, Sylvia atricapilla, Spilopelia senegalensis, Columba livia, and Coloeus monedula were encountered in green gardens; four species counting Athene noctua, Sturnus unicolor, Passer domesticus, and Tachymarptis melba were observed in old city walls. Falco tinnunculus, Fringilla coelebs, and Accipiter nisus occurred in urban forests; and Streptopelia decaocto in urban farms. The recorded nests were divided between cavities (50 nests) and trees (59 nests). In green spaces, nests were distributed among Olea europaea (17), Citrus aurantium (15), Bambusa vulgaris (11), and Eucalyptus globulus (7). In contrast, Olea oleaster and Cupressus sp. hosted only tree nests each, while Populus sp. and Washingtonia filifera hosted only one nest each. Most nests were recorded in habitats rich in nesting trees and close to water sources. On the contrary, the number of nests decreased as the surface and distance of the habitat to the urban center increased. Our data revealed the diversity, habitat use, and nesting substrates of urban breeding bird communities in Morocco and the Southern slope of the Western Palearctic. Future urban plans must integrate measures to provide suitable breeding resources such as cavities of old walls and a high diversity of urban green spaces for birds to enhance their breeding performances, thus promoting the well-being of the population via increasing biodiversity.